Designing for Educational Technology to Enhance the Experience of Learners in Distance Education: How Open Educational Resources, Learning Design and Moocs Are Influencing Learning. Issue 1 (10th April 2015) - Scanlon, Eileen; McAndrew, Patrick; O'Shea, Tim
The area of learning has a justifiable claim to be a special case in how it can be enhanced or supported by technology. In areas such as commerce and web design the aim is usually to ensure efficiency and support specific actions such as purchasing or accessing information as quickly and easily as possible. Working with technology for the purpose of learning, the user is expected to spend time facing challenges, struggling through them and in almost every case the interaction with the technology is only one of many influences in achieving success. This does not mean that computing and the Internet has not had a major impact on how we learn and the choices available to learners. On the contrary, the area of formal learning is undergoing a period of rapid change, and the barriers between formal and informal learning are showing signs of falling away, in part due to the changes in the access to information or alternative modes of delivery. The influence of technology on pedagogy (the manner or structure of teaching) is complex. There is relatively little direct research on the ways that technological possibilities and the pedagogical response to these operate to benefit the lifelong learner. In this article we are bringing together the evidence from strands of research based on work in online and distance learning in formal settings, and also on open and free online education, which is often less formal. This research sheds light on several factors relevant to the outcomes of instruction: the often unpredictable motivations of learners, the trajectories they take through courses, and the indicators for success in formal and informal learning, in terms of both pedagogy and technology. We present the outcomes of practical endeavours to widen access to education using technology which indicate that open education is offering alternative ways of supporting learners. These suggest a focus on design decisions that can help integrate the process of learning more closely with ways in which online systems currently support learning and the data that can be used to interpret how well those designs are working.